2011
DOI: 10.1007/s10551-011-1096-2
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Behavioral Intentions in Macedonia: Coping Strategies, Work Environment, Love of Money, Job Satisfaction, and Demographic Variables

Abstract: Based on theory of planned behavior, we develop a theoretical model involving love of money (LOM), job satisfaction (attitude), coping strategies/responses (perceived behavioral control), work environment (subjective norm), and work-related behavioral intentions (behavioral intention). We tested this model using job satisfaction as a mediator and sector (public versus private), personal character (good apples versus bad apples), gender, and income as moderators in a sample of 515 employees and their managers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 110 publications
3
22
1
7
Order By: Relevance
“…The work carried out by the State Polytechnic lecturers of Malang, which is teaching and guiding the students, was in accordance with what they expected, so that Job Satisfaction which the lecturers of Malang State Polytechnic improved. The results of this study are in line with several previous studies conducted byAbuAlRub, et al 2016, Jain, et al (2014), Raziq and Maulabakhsh (2015), dan Sardzoska and Tang (2012),which shows that physical Work Environment and non-physical Work Environment affect Job Satisfaction of lecturers.…”
Section: Effect Of Work Environment On Job Satisfactionsupporting
confidence: 92%
“…The work carried out by the State Polytechnic lecturers of Malang, which is teaching and guiding the students, was in accordance with what they expected, so that Job Satisfaction which the lecturers of Malang State Polytechnic improved. The results of this study are in line with several previous studies conducted byAbuAlRub, et al 2016, Jain, et al (2014), Raziq and Maulabakhsh (2015), dan Sardzoska and Tang (2012),which shows that physical Work Environment and non-physical Work Environment affect Job Satisfaction of lecturers.…”
Section: Effect Of Work Environment On Job Satisfactionsupporting
confidence: 92%
“…Love of money (LOM) is defined as one's attitudes toward money with affective, behavioral, and cognitive components and as a multi-dimensional individual difference variable (Tang & Chen, 2008). Scholars have substantiated this construct in empirical studies across almost three dozen countries around the world (Sardžoska & Tang, 2012;Tang & Liu, 2012;Tang & Sutarso, in press;Tang et al, 2006;Wong, 2008), cited in influential reviews (Kish-Gephart, Harrison, & Treviño, 2010;Mitchell & Mickel, 1999), and mentioned in numerous books (Colquitt, LePine, & Wesson, 2013;Furnham & Argyle, 1998;McShane & Von Glinow, 2013;Milkovich, Newman, & Gerhart, 2011;Rynes & Gerhart, 2000).…”
Section: The Love Of Money (Lom)mentioning
confidence: 99%
“…Work stress also equates with job unhappiness, frustration, or dissatisfaction (Giauque, Anderfuhren-Biget, and Varone 2013;Zhang, Yao, and Cheong 2011), and inevitably aligns with negative mental or physical health consequences. Empirical research has found that a high level of work stress on the part of public employees can undermine public sector efficiency and effectiveness (McHugh and Brennan 1994) and even lead to counterproductive behavior (Sardžoska and Tang 2012). Conversely, job satisfaction relates positively to officials' ethical behavior (Brown, Treviño, and Harrison 2005;Kim and Brymer 2011).…”
Section: Work-related Well-beingmentioning
confidence: 99%